Establishment, Prediction, and Validation of a Nomogram for Cognitive Impairment in Elderly Patients With Diabetes - Sensen Wu; Dikang Pan; Hui Wang; Julong Guo; Fan Zhang; Yachan Ning; Yongquan Gu; Lianrui Guo (Journal of Diabetes Research)
Conclusion: The newly developed nomogram has proved to be an important tool for accurately predicting cognitive impairment in elderly patients with diabetes, providing important information for targeted prevention and intervention measures.